2020
DOI: 10.1136/bmj.m791
|View full text |Cite
|
Sign up to set email alerts
|

Global, regional, and national burden of neck pain in the general population, 1990-2017: systematic analysis of the Global Burden of Disease Study 2017

Abstract: Objective To use data from the Global Burden of Disease Study between 1990 and 2017 to report the rates and trends of point prevalence, annual incidence, and years lived with disability for neck pain in the general population of 195 countries. Design Systematic analysis. Data source Global Burden of Diseases, Injuries, and Risk Factors Study 2017. Main outcome measures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
289
2
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 387 publications
(320 citation statements)
references
References 20 publications
16
289
2
13
Order By: Relevance
“…According to a recent study, the prevalence and incidence of LBP ranged from 1.4% to 20% and from 0.024% to 7%, respectively, in workers [ 26 ]. The overall mean prevalence of neck pain in the general population is 3.6% [ 27 ], with a higher incidence in office and computer workers [ 28 ]. Italian estimated lifetime prevalence is 9% for LBP and 5% for neck pain [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent study, the prevalence and incidence of LBP ranged from 1.4% to 20% and from 0.024% to 7%, respectively, in workers [ 26 ]. The overall mean prevalence of neck pain in the general population is 3.6% [ 27 ], with a higher incidence in office and computer workers [ 28 ]. Italian estimated lifetime prevalence is 9% for LBP and 5% for neck pain [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Between 50% and 85% of the general population experience neck pain at some point in their lives and every person who experiences neck pain is likely to experience it again 1-5 years later [1]. A recent study [2] showed that the prevalence, incidence and years lived with disability from 1990 to 2017 has not changed significantly from the previous report [3]. The global prevalence was 3.5%, 288.7 million cases, from which 65.3 million cases were incident and 28.6 million spent years living with a disability.…”
Section: Introductionmentioning
confidence: 99%
“…Neck pain is a common condition that leads to serious pain, disability, and increased healthcare costs worldwide [1][2][3]. Increasingly more researchers are finding that effective treatment and prevention strategies for neck pain are needed [1,4].…”
Section: Introductionmentioning
confidence: 99%
“…Neck pain is a common condition that leads to serious pain, disability, and increased healthcare costs worldwide [1][2][3]. Increasingly more researchers are finding that effective treatment and prevention strategies for neck pain are needed [1,4]. Pharmacotherapy, including opioids, non-steroidal anti-inflammatory drugs (NSAIDs), and paracetamol, is one of the most common strategies to reduce neck pain reduction in the USA [5,6].…”
Section: Introductionmentioning
confidence: 99%